Medium-energy microprobe station at the SXRMB of the CLS - Xiao, Q.; MacLennan, A.; Hu, Y.; Hackett, Mark; Leinweber, P.; Sham, T. (2017)
Micro-XAFS and chemical imaging techniques have been widely applied for studies of heterogeneously distributed systems, mostly in hard X-ray (>5 keV) or in soft X-ray (<1.5 keV) energies. The microprobe endstation of the SXRMB (soft X-ray microcharacterization beamline) at the Canadian Light Source is optimized at the medium energy (1.7-5 keV), and it has been recently commissioned and is available for general users. The technical design and the performance (energy range, beam size and flux) of the SXRMB microprobe are presented. Examples in chemical imaging and micro-XAFS in the medium energy for important elements such as P, S and Ca for soil and biological samples are highlighted.